Teens in South Africa - David Seidman (Minneapolis, MN, United States COMPASS POINT BOOKS, 2009)
South Africa is home to nearly 7 million teens, the first generation in 50 years to grow up without the division of apartheid. Though South Africa is one of the wealthiest sub-Saharan countries in Africa, its young people face problems such as poverty, pregnancy, and the AIDS epidemic. Still, they find happiness in their friends, families, music, and sports. Teens in South Africa is part of Global Connections, a series that uncovers the challenges, pastimes, and customs of teens around the world.
Keywords: Non Fiction